Investigation of dielectric properties of starch nanoparticles derived from arrowroot (Maranta arundinaceae L.) rhizomes - M. Ramya; Rajita Ramanarayanan; S. Esakki Muthu; Karthik Kannan; Jhelai Sahadevan; A. Dinesh; Lalitha Gnanasekaran; Manikandan Ayyar; S. Santhoshkumar (Results in Chemistry)
This study presents a novel, green approach to tailoring the dielectric properties of starch by mechanical means alone, without chemical modification. The correlation between ball milling-induced structural changes and dielectric performance is reported for the first time using native arrowroot starch, highlighting its potential as a sustainable material for eco-friendly electronic applications. The structure and characteristics of starch granules are drastically changed by ball milling. Ball milling reduces granule size and produces irregular, porous structures by destroying the spherical or oval geometry of raw starch (SR), according to SEM pictures. The XRD study reveals decrease of crystallinity from 28 % (SR) to 13 % (milled starch, SM), and the peaks that were typical of A-type starch vanished, signifying amorphization. The binding energies of the C1s and O1s peaks fluctuate in the XPS measurements, indicating oxidation state alterations and bond rupture. Raman spectroscopy, which shows a weakening of vibrational signals, further validates structural amorphization. Due to structural disturbance and decreased interfacial polarisation, dielectric measurements reveal decreased impedance, dielectric constant, and loss factor for SM. Due to higher resistance, SM has lesser electrical conductivity than SR. With SM showing a wider semicircle, which denotes more resistance and decreased charge carrier mobility, the Cole-Cole plot shows changed relaxation behaviour.